2012
DOI: 10.1074/jbc.m111.336537
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Processing and Function of Human and Ferret Cystic Fibrosis Transmembrane Conductance Regulator

Abstract: Background: Species-specific differences in WT-and ⌬F508-CFTR biology exist. Results: Ferret WT-CFTR displays enhanced maturation efficiency and post-Golgi stability relative to human. Ferret ⌬F508-CFTR maturation was greater than human in certain cell lines; both orthologs lacked function in airway epithelia. Conclusion: Ferret and human CFTR have unique differences in processing and stability. Significance: Generation of a ⌬F508-CFTR ferret animal model may be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 35 publications
(31 reference statements)
5
26
0
1
Order By: Relevance
“…Short-circuit current (I SC ) was measured using a VCC MC8 Multichannel voltage/ current clamp (Physiologic Instruments, San Diego, CA) as previously reported (19,20). For more details, see the MATERIALS AND METHODS in the online supplement.…”
Section: Electrophysiologic Studiesmentioning
confidence: 99%
“…Short-circuit current (I SC ) was measured using a VCC MC8 Multichannel voltage/ current clamp (Physiologic Instruments, San Diego, CA) as previously reported (19,20). For more details, see the MATERIALS AND METHODS in the online supplement.…”
Section: Electrophysiologic Studiesmentioning
confidence: 99%
“…All tissues were harvested into Ringer's solution containing 1 mM indomethacin, and this level of indomethacin was maintained throughout the experiment to eliminate stimulation of cAMP production by endogenous prostaglandins (22,38). I SC and resistances (R) were measured using a VCC MC8 Multichannel voltage/current clamp (Physiologic Instruments) as previously reported (10,39). For more details on electrophysiologic measurements see the online supplement.…”
Section: Ussing Chamber Analysismentioning
confidence: 99%
“…To date, there are three reported species of CF animal models, including the mouse, pig, and ferret (5)(6)(7)(8). Characterization of each of these models has clearly demonstrated that species-specific differences in organ physiology and CFTR biology influence the extent of pathologic and electrophysiologic changes observed when CFTR is deleted or mutated (8)(9)(10)(11). CF ferrets have been shown to develop intestinal complications, diabetes, pancreatic disease, absence of the vas deferens, growth retardation, liver disease, and an elevated risk of developing lung infections (9,(11)(12)(13).…”
mentioning
confidence: 99%
“…Studies in animal models for CF with modification of CFTR develop multi-system disease, including pancreas and lung disease that have very similar pathology to that in patients (47,48,49). Endocrine pancreas function in the CFTR-null ferret is abnormal from birth, which suggests that it is an intrinsic defect in b-cell function in CF (47). In the same way as in humans, the glucose abnormalities progress with age in the Cftrnull animals as pancreatic fibrosis worsens.…”
Section: B-cell-specific Dysfunctionmentioning
confidence: 93%
“…For these patients, impaired insulin secretion is mostly apparent during the first phase, strongly indicating a defect at the level of the pancreatic b-cell. Studies in animal models for CF with modification of CFTR develop multi-system disease, including pancreas and lung disease that have very similar pathology to that in patients (47,48,49). Endocrine pancreas function in the CFTR-null ferret is abnormal from birth, which suggests that it is an intrinsic defect in b-cell function in CF (47).…”
Section: B-cell-specific Dysfunctionmentioning
confidence: 99%